Al Ṭibāqu fī al Aḥādiṡi al Syarīfati fī Kitābi Riyāḍi al Ṣāliḥīna li Syaikhi al Islāmy Muḥyiddīn Abī Zakariyyā’i Yaḥyā Ibni Syarafi al Nawawī - Mahendra, M. Ysril Iza; Buska, Wahyudi (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
This research aims to reveal the implementation of the use of the book of Riyadus Salihin. Riyadus Salihin is a book of hadist that contains the hadith of the Prophet Muhammada SAW, consisting of 546 chapters that begin with a sincere chapter and present intentions in all activities and end with baba pa that Allah the Exalted has provided for believers in heaven, the book of Riyadus Salihin contains 1897 hadist derived from scholarly sources such as Saheeh Muslim, Sunan Abu Daud At Tarmizi and also Shahih Bukhari. This study aims to recognize the opposite words in the book of Riyadus Salihin with the analysis of the Science of Balaghah, as in the 2nd order hadist there are opposite beginning and end words. This research uses descriptive methods and qualitative approaches by collecting books and books related to this research. The results of the study were 27 Thibaq Ijabi and 3 Thibaq Salbi.